Early postoperative parathormone sampling and prognosis after total parathyroidectomy in secondary hyperparathyroidism - Nascimento Júnior,Climério Pereira do (2017)
Abstract Introduction: There is possibility of a supernumerary hyperplastic parathyroid gland in dialysis patients after total parathyroidectomy and autograft in dialysis patients. Objective: To test if the early postoperative measure of parathyroid hormone (PTH) can identify persistent hyperparathyroidism. Methods: A prospective cohort of dialysis patients submitted to parathyroidectomy had PTH measured up to one week after operation. The absolute value and the relative decrease were analyzed according to clinical outcome of satisfactory control of secondary hyperparathyroidism or persistence. Results: Of 51 cases, preoperative PTH varied from 425 to 6,964 pg/mL (median 2,103 pg/mL). Postoperatively, PTH was undetectable in 28 cases (54.9%). In eight individuals (15.7%) the PTH was lower than 16 pg/mL, in 10 (19.6%) the PTH values were between 16 and 87pg/mL, and in five (9.8%), PTH was higher than 87 pg/mL. Undetectable PTH was more common in patients with preoperative PTH below the median (p = 0.0002). There was a significant correlation between preoperative PTH and early postoperative PTH (Spearman R = 0.42, p = 0.002). A relative decrease superior to 95% was associated to satisfactory clinical outcome. A relative decrease less than 80% was associated to persistent disease, despite initial postoperative hypocalcemia. Conclusion: Measurement of PTH in the first days after parathyroidectomy in dialysis patients may suggest good clinical outcome if a decrease of at least 95% of the preoperative value is observed. Less than 80% PTH decrease is highly suggestive of residual hyperfunctioning parathyroid tissue with persistent hyperparathyroidism, and an early reintervention may be considered.